ADHD severity as a predictor of cognitive task performance in children with Autism Spectrum Disorder (ASD). (April 2021) - Mansour, Rosleen; Ward, Anthony R.; Lane, David M.; Loveland, Katherine A.; Aman, Michael G.; Jerger, Susan; Schachar, Russell J.; Pearson, Deborah A.
Abstract: Background: In recent years, a number of studies have begun to explore the nature of Attention-Deficit/Hyperactivity Disorder (ADHD) in children with Autism Spectrum Disorder (ASD). In this study, we examined the relationship between both symptoms of ADHD and symptoms of ASD on cognitive task performance in a sample of higher-functioning children and adolescents with ASD. Participants completed cognitive tasks tapping aspects of attention, impulsivity/inhibition, and immediate memory. Aims: We hypothesized that children with ASD who had higher levels of ADHD symptom severity would be at higher risk for poorer sustained attention and selective attention, greater impulsivity/disinhibition, and weaker memory. Methods and procedures: The sample included 92 children (73 males) diagnosed with ASD (Mean Age = 9.41 years; Mean Full Scale IQ = 84.2). Outcomes and results: Using regression analyses, more severe ADHD symptomatology was found to be significantly related to weaker performance on tasks measuring attention, immediate memory, and response inhibition. In contrast, increasing severity of ASD symptomatology was not associated with higher risk of poorer performance on any of the cognitive tasks assessed. Conclusions and implications: These results suggest that children with ASD who have more severe ADHD symptoms are at higher risk for impairments in tasks assessing attention, immediate memory, and response inhibition—similar to ADHD-related impairments seen in the general pediatric population. As such, clinicians should assess various aspects of cognition in pediatric patients with ASD in order to facilitate optimal interventional and educational planning.